Midwifery Care For Women In Labor With A Mother-Loving Approach - Rahmiyani Saad; Kiki Uniatri Thalib; Sulistyani Prabu Aji (International Journal of Health Sciences, 2026)
The Mother-Friendly approach is a midwifery service concept that emphasizes fulfilling the physical, psychological, social, and cultural needs of mothers during the labor process. This approach aims to create a safe, comfortable, dignified, and mother-centered labor experience. This study aims to describe the implementation of midwifery care for mothers giving birth using the Mother Friendly approach. The study used a descriptive design with a case study approach. The research subject was a mother giving birth in the first–fourth stage who received midwifery care using the Mother Friendly approach at Community Health Center X. Data collection was carried out through interviews, observations, physical examinations, and SOAP documentation. The results of the study indicate that the implementation of the Mother Friendly approach can increase comfort, reduce anxiety, and support a physiological labor process. It was concluded that the Mother Friendly approach is effectively implemented in midwifery care for mothers giving birth.